Perbedaan Pengaruh Pemberian Infra Red (IR) Dan Transcutaneus Electrical Nerve Stimulation (TENS) Dengan Neuromuscular Taping (NMT) Terhadap Penurunan Nyeri Low Back Pain (LBP) Myogenik - Wardani, Mulyaningtyas Trikusuma; , Umi Budi Rahayu,S.Fis,M.Kes (2016)
Background:LBP myogenik is lower back pain caused by excessive muscle tension that will cause pain. To deal with complaints of pain in LBP physioterapy can provide modalities often used reduce pain is Transcutaneus Electrical Nerve Stimulation (TENS) andInfra Red (IR). Besides modalities usually used there is also a new method that is Neuromuscular Tapping (NMT) on the reduction of pain in patients LBP myogenik. NMT is a techniue that involves applying elastic adhesive tape on the skin,provides local therapuetic effect,and reduce pain. Objective:The difference between the effect of the provision of routine physiotherapy and Neuromuscular Tapping (NMT) to a decrease in pain in cases of Low Back Pain (LBP) myogenik. Method :Type of research is an experimental approach to design Quasi Eksperimental study pre post test two group design.responden of this studies as many as 20 people were divided into two groups. 10 in the control group and 10 in the treatment group.The research was done 2 times a week for 4 week.Measurement pain do is Visual Analog Scale (VAS) with analysis techniQues use test wilcoxon signed rankand mann whitney. Result and Discussion:in the control group mean pre test 6.62 andpost test 5.74,while in the treatment group mean pre test 6.53andpost test 4.24. Based on the statistical obtained wilcoxon signed rankavailable p-value in the group control 0,007 andp-value in thegroup treatment 0,005 andthe test statistik mann whitney avaiblep-value 0,000. Conclusion different influences between physiotherapy routine and NMT to reduces pain LBP myogenik.